Effect of Silver Diamine Fluoride Pretreatment on Shear Bond Strength of Resin Modified Glass Ionomer Cement to Primary Dentin - Sa’ada, Maiada Mohammad Ahmad; Khattab, Nagwa Mohammed Ali; Amer, Maha Ishaq (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The aim of the study was to evaluate effect of silver diamine fluoride (SDF) on the shear bond strength (SBS) of glass ionomer restoration to primary dentine. MATERIALS AND METHODS: Twenty extracted primary molars with no restorations or developmental anomalies were only chosen for the study. Twenty dentine slices with 2 mm thickness were prepared and then randomly allocated into two groups (n = 10 per group). For Group 1 (experimental): Dentine surfaces were treated with 38% *SDF solution (Elevate oral care, USA) for 3 min using micro-brush, followed by a 30 s rinse with water and Group 2 (Control): Dentine surfaces were treated with distilled water for 3 min then rinsed for 30 s. The cavity conditioner was applied to flat dentin of both groups for 10 s then washed and dried gently with compressed air. All the specimens were restored with *RMGIC (Riva Light Cure, SDI, Australia). SBS was determined using a Universal Testing machine and Failure mode was evaluated using stereomicroscope. Data were collected and statistically analyzed. Independent t test was used to assess differences in SBS between study groups and mode of failure was analyzed using Fisher’s exact test. Level of significance was set at p ≤ 0.05. IBM SPSS statistical software (version 26) was used to analyze the data. RESULTS: The experimental group had significantly higher mean of shear bond (11.92 ± 3.35) strength than the control group (6.99 ± 2.98) (p = 0.003). CONCLUSIONS: Primary dentin pre-treatment with 38% SDF increases the shear bond strength between RMGIC and primary dentin according to the results of this in vitro study.